Can the Poor Participate in Payments for Environmental Services? Lessons from the Silvopastoral Project in Nicaragua - Pagiola, Stefano (2012)
This paper uses data from a Payments for Environmental Services (PES) project being implemented in Nicaragua to examine the extent to which poorer households that are eligible to participate are in fact able to do so, an issue over which there has been considerable concern. The study site provides a strong test of the ability of poorer households to participate, as it requires participants to make substantial and complex land use changes. The results show that poorer households are in fact able to participate--indeed, by some measures they participated to a greater extent than better-off households. Moreover, their participation was not limited to the simpler, least expensive options. Extremely poor households had a somewhat greater difficulty in participating, but even in their case the difference is solely a relative one. Transaction costs may be greater obstacles to the participation of poorer households than household-specific constraints.